THE HISTORY OF WEAVING CRAFTS IN MUNA - Jamiludin Jamiludin; La Ode Dinda (Universitas Padjadjaran, 2022)
The objectives of this study are: (1) to explain the history of the origins of the Muna weaving craft, (2) The process of making Muna woven fabrics, (3) The function of woven fabrics in Muna society. This study used historical method and a descriptive qualitative approach. The number of respondents was 15 weaving craftsmen. The results of this study explained that: (1) the history of the origin of the Muna weaving craft and this craft is one of their activities used in certain events. (2) The craft was carried out in two stages in weaving and using two energies, namely the straightening stage (desoro) and the weaving stage (domooru). (3) Weaving craft in Muna society has aesthetic, symbolic, religious, social status for the men, women, and children.